T76. THALAMO-CORTICAL ABNORMALITIES IN SCHIZOTYPAL PERSONALITY DISORDER AND SCHIZOPHRENIA. (9th April 2019) - Hazlett, Erin; Tang, Cheuk; Wong, Edmund; Chan, Chi; Zinn, Kim; Vaccaro, Daniel; Szeszko, Philip; Chu, King-Wai
Abstract: Background: Although several studies report thalamo-cortical abnormalities in schizophrenia, there is a paucity of functional neuroimaging work in schizotypal personality disorder (SPD) examining these networks despite the advantage of being able to study unmedicated and primarily never-medicated participants. SPD is a schizophrenia spectrum disorder that shares common phenomenological, genetic, and biological characteristics with schizophrenia. Methods: This presentation will review prior schizophrenia-spectrum work examining thalamo-cortical connectivity and present new fMRI findings in a relatively large demographically-matched spectrum sample with three diagnostic groups: 24 schizophrenia patients, 54 individuals with SPD, and 48 healthy controls (without Axis I or personality disorder diagnosis). Participants received a rigorous structured diagnostic interview, clinical assessments, and a 3T structural MRI and resting-state fMRI scan at Mount Sinai Hospital. Bilateral seed-based analyses were conducted using the whole thalamus as the seed. Group analysis was performed using FSL-FEAT with p-values set to p<0.05 (corrected). Results: Compared with the healthy controls, both the SPD and schizophrenia groups had greater whole thalamus connectivity with the temporal lobe, primarily in the middle temporal gyrus. Schizophrenia patients showed reduced thalamo-frontal connectivity compared with the healthy controls, primarily in the superior frontal gyrus and dorsolateral prefrontal cortex. In contrast to schizophrenia patients, the SPD group did not differ from normal in thalamo-frontal connectivity. Discussion: These schizophrenia spectrum findings are consistent with prior work showing reduced thalamo-frontal connectivity. The novel findings from this three-group comparison within the schizophrenia spectrum pertain to the SPD group and indicate: (1) similarities in thalamo-temporal abnormalities across SPD and schizophrenia, suggesting this may be a shared schizophrenia spectrum neurobiological trait marker; and (2) normal thalamo-frontal connectivity in SPD which may be a protective factor from frank psychosis. Symptom severity correlates of thalamo-cortical functional connectivity will also be presented.